ANALISIS FILTER INDUKTIF DAN KAPASITIF PADA CATU DAYA DC - Sollu, Tan Surayani (MEKTEK, 2010)
One of the main component of DC power supply is filter, which consist of inductor and capacitor, that has function to smooth out the ripples voltage so that it can be obtained stable pure DC signals. There are four types of filter with the same input condition analysed in the research, (1) inductive filter, (2) capacitive filter, (3) L-form inductive filter, (4) Ï€-form capacitive filter. The obtained result indicate that capasitive filter output voltage is bigger and more stable than inductive filter. The biggest output voltage (9,21 Volt) and smallest ripples factor (r=0,0003) are resulted by Ï€-form, capasitive filter. In the certain range, the greater of capacitansi value, the smaller of the ripple factor and the output sinyal is more stable.